Commodification of Human Body and Consciousness in Black Mirror Season 7, Episode 1, Common People - Wati Purnama Sari (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research analyzed Black Mirror season 7 series, episode 1 entitled Common People, using Vincent Mosco’s concept of commodification. A qualitative method is used in this research. There are 44 data found. The data were coded into three categories: audience commodification (21 data), content commodification (18 data), and labour commodification (5 data). The findings indicated that audience commodification was the most dominant form. The data showed that both the body and consciousness of the user are absorbed into commercial systems. The user’s body is turned into a source of energy and a channel for advertisement, while the user’s consciousness offered for advertising and something controlled through subscriptions. The company intended to turn the audience into a commodity. Therefore, Black Mirror season 7 series, episode 1 entitled Common People delivers a strong critique of the growing commercialization of human body and consciousness in the technological development.